1993
DOI: 10.1128/aem.59.6.1813-1820.1993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacterial Biomass on Contaminant Sorption and Transport in a Subsurface Soil

Abstract: The objective of this study was to investigate the impact of bacterial biomass on the sorption and transport of three solutes (quinoline, naphthalene, and 45Ca) in a subsurface soil. Miscible displacement techniques were employed to measure sorption and transport of the above compounds during steady, saturated water flow in sterile and/or bacterium-inoculated soil columns. The soil was inoculated with either a quinoline-degrading bacterium, Pseudomonas sp. 3N3A isolate, or its mutant isolate, B53, which does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…In a review paper, Baughman and Paris [1981] concluded that sorption of organic solutes occurs on the cell surfaces (biosorption). Similar conclusions were later reached by other researchers with a variety of organic substances such as lindane, pentachlorophenol, and diazinon [Bell and Tsezos, 1987;Tsezos and Bell, 1989;McRea, 1985]. Lindqvist and Enfield [1992] reported that biosorption of organic compounds is a passive, physical phenomenon rather than an active, biological one.Bellin and Rao [1993] noted that the presence of both bacteria and contaminant in subsurface environment may result in 321 CONTAMINANT TRANSPORT 331…”
supporting
confidence: 66%
“…In a review paper, Baughman and Paris [1981] concluded that sorption of organic solutes occurs on the cell surfaces (biosorption). Similar conclusions were later reached by other researchers with a variety of organic substances such as lindane, pentachlorophenol, and diazinon [Bell and Tsezos, 1987;Tsezos and Bell, 1989;McRea, 1985]. Lindqvist and Enfield [1992] reported that biosorption of organic compounds is a passive, physical phenomenon rather than an active, biological one.Bellin and Rao [1993] noted that the presence of both bacteria and contaminant in subsurface environment may result in 321 CONTAMINANT TRANSPORT 331…”
supporting
confidence: 66%
“…Furthermore, the introduction of genetically engineered exogenous bacteria in a bioremeCliation operation can short-circuit the effort by biocolloid-facilitated contaminant transport. Recently, Bellin and Rao [1993] noted that the presence of bacteria in subsurface environments may affect polynuclear aromatic hydrocarbon (PAH) migration by altering the sorption characteristics of soil solids. Jenkins and Lion [1993] have indicated that bacteria may enhance the transport of PAHs in the subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…For some problems, such as pollution of drinking water by pathogenic bacteria from leaking septic tanks and landfills [Gerba and Bitton, 1984;Yates and Yates, 1988], limited microbial mobility may be preferred, whereas for other applications, such as in situ bioremediation of polluted aquifers, high mobility is advantageous, since the success of remediation procedures depends on the ability to transfer bacteria to the contaminated areas in the aquifer [Harvey, 1991]. However, mobile bacteria may enhance the transport of, for example, hydrophobic trace contaminants [Lindqvist and Enfield, 1992a], ionizable organic bases [Bellin and Rao, 1993], and radionuclides [Champ, 1986], so predictive models of bacterial dispersal in porous media are needed to estimate both the efficiencies and risks of aquifer bioremediation schemes [Tiedje et aI., 1989] and the risks of bacterial contamination of drinking water.…”
Section: Introductionmentioning
confidence: 99%